Report of the Sub-Group of Chief Ministers on Skill Development - NITI Aayog (NITI Aayog, Government of India)
India enjoys the demographic advantage of having the youngest workforce with average age of 29 years in comparison with the advanced economies. It can be the Human Resource Capital of the world by appropriately skilling its youth bulge and convert its advantage into a dividend. However, skilling this huge labour force is a challenge given the low levels of vocational training in India, high proportion of school-dropouts, huge informal workforce, poor quality of training etc. The question is not only of fresh skilling but also up skilling I re-skilling of the existing workers to make them compatible with the changing needs of the industry and market requiring a Mission mode approach.
NITI Aayog, Government of India
Keywords: Skill Development